An investigation of the long-run relationship between import tariff, import quantity, production and prices in the broiler section of South Africa (April 2010-June 2022) - Nkgadima, Kgothatso (My University, 2022)
The agricultural sector is dominated by broiler production and it is the key source of animal proteins followed by beef. South Africa is described as a net importer of chicken meat, given that broiler consumption of broiler is greater than supply. Additionally, the South African Poultry industry has raised concerns regarding the high influx of cheap broiler imports into the domestic market. This led to an increase of the ad valorem tariff charged on poultry imports in April 2020 from a previous adjustment in September 2013. It is vital to understand how import tariff changes affect the broiler sector since little is known about how domestic broiler production is responding to an increased tariff. The study, therefore, attempted to determine the relationship between domestic broiler production, import tariff, domestic prices, and import volume. The study aimed to investigate the long-run relationship between import tariff, import quantity, domestic production, and prices (retail and producer) in the broiler sector of South Africa for the period (April 2010 – June 2020). Brazilian frozen chicken imports were selected for study given their relatively high domestic demand in South Africa. In addition, Brazil primarily faces the import tariffs charged by South Africa as the main country of origin for South African imports. The Augmented Dickey-Fuller test, Johansen Cointegration tests, and the Error Correction Model were used as analytical tools in achieving the study objectives. The results for the Augmented Dickey-Fuller test and the Johansen cointegration test showed that all variables were stationary at first difference and cointegrated. The ECM results concluded the existence of a long-run relationship between domestic production, ad valorem tariff, and import volume. As the tariff charged changes, the domestic production increased by 4% in the long run which might be deemed a small advantage in terms of the production scale and therefore not sufficient. The study recommended that strategies that reduce barriers of entry for small-scale farmers such as reduced production costs be implemented to boost domestic production. Lastly, since domestic production is responding positively to tariff adjustment, a thorough investigation is necessary to prove dumping allegations against broiler importers as this will enable the country to impose anti-dumping duties on all countries.
Thesis (M.Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2022
Keywords: Frozen chicken; Long-run relationship; Ad valorem tariff; ECM; Frozen chicken; Poultry -- Breeding -- South Africa; Chickens -- Breeding